MANAJEMEN PERSONALIA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Muhammad Madarik (Jurnal Studi Pesantren, 2026)
Human resource management is a crucial aspect of any organization. Personnel management becomes important in the context of personnel empowerment. Personnel management from an Islamic educational perspective can be explained as follows: (1) Personnel who have competence. (2) Personnel who carry out tasks. (3) Personnel who are professional. (4) Personnel who have leadership skills. The steps in the personnel preparation process as the implementation of personnel management in Islamic education are: (1) Human Resources Planning [QS. Al-Mujadilah: 11]. (2) Withdrawal or Recruitment [QS. Al-Baqarah: 159]. (3) Selection [QS. Al-Qashash:26]. (4) Introduction and Orientation [Al-An'am:165]. (5) Training and Development [QS. Al-Isra: 70]. (6) Work Implementation Assessment [QS. Az-Zalzalah:7-8]. (7) Providing Remuneration and Awards [QS. Al-Qashash]. (8) Career Development [QS. Al-An'am: 132]. The conclusion is that personnel development must be colored by Islamic values as an implementation of personnel management in Islamic education.